Do Export Learning Processes Affect Sales Growth in Exporting Activities?. Issue 3 (September 2019) - Assadinia, Shahin; Boso, Nathaniel; Hultman, Magnus; Robson, Matthew
The understanding of experiential learning through export learning process (XLP), and its outcomes, is limited in the international marketing literature. Using multisource, time-lagged data of exporting firms in the United Kingdom and China, this study finds that XLP is positively associated with marketing strategy adaptation for both U.K. and Chinese exporters. Results suggest contrasting moderating effects of experiential knowledge resources (i.e., psychic dispersion, multinationality, and duration) and strategy adaptation on the relationship between XLP and export sales growth in the two samples. In the U.K. sample, the authors observe a positive moderation effect of psychic dispersion and negative moderation effects of multinationality and duration. For the China sample, they find the exact opposite pattern of moderation effects for the experiential knowledge resources. Marketing strategy adaptation plays a negative moderation role in the China sample but has no such effect in the U.K. sample. The study has implications for theory development on, and the productive management of, processes of learning export management.